Analisis Yuridis terhadap Tindakan Bullying di Lingkungan Sekolah Ditinjau dari Undang-Undang 35 Tahun 2014 Tentang Perlindungan Anak Studi pada MIS Bina Bangsa - Ahmilla Kusfadia; Akiruddin Ahmad; Zuhri Arif (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze bullying in the school environment as a violation of children's rights based on Law Number 35 of 2014 concerning Child Protection and to examine the forms of legal protection provided by schools to victims of bullying at MIS Bina Bangsa. This research is empirical legal research using a juridical-empirical approach, which examines the implementation of legal norms in real conditions. Data were collected through interviews, observations, and documentation studies, and analyzed qualitatively. The results show that bullying at MIS Bina Bangsa occurs in verbal, physical, cyberbullying, and psychological forms, which constitute violations of Article 59, Article 76C, and Article 76D of Law Number 35 of 2014. Legal protection efforts implemented by the school include teacher supervision, character education, anti-bullying socialization, and coordination with parents. However, these efforts have not been optimally implemented due to the absence of standardized operating procedures (SOPs) for handling bullying cases. Practically, this study implies the need for schools to formulate clear anti-bullying SOPs, strengthen teachers’ capacity in identifying and handling bullying cases, enhance collaboration with parents, and integrate child protection principles into school policies. These findings are expected to contribute to strengthening child protection mechanisms in primary educational institutions.